Chirps and Silence: A Study of Ecocriticism in Poetry’s by Sugiarto B. Darmawan - Onok Yayang Pamungkas (CV. Rustam, 2024)
In an era where environmental degradation is accelerating due to human activities, research on ecology has become very important. For this reason, Sugiarto B. Darmawan's poems are important to explore the relationship between humans and nature. The purpose of this research is to explore the poems of Sugiarto B. Darmawan in the perspective of literary ecocriticism. The research data source is a poem by Sugiarto B. Darmawan published in the Borobudur Festival Writers. The research method uses hermeneutics. The study results show that the poems by Sugiarto B. Darmawan represent environmental wisdom. Literary ecocriticism in Sugiarto B. Darmawan's poem describes the beauty and diversity of nature and its interaction with human life. In his poems, Sugiarto B. Darmawan lovingly and appreciatively describes the flora and fauna that adorn the surrounding nature, from the birds that enliven the morning with their chirping, to the various types of trees and plants that cover the hills and valleys. These poems invite readers to reflect on the importance of maintaining the balance of nature. The lives of animals and plants described in his poem show how nature and humans are interdependent. A harmonious life in nature reflects the balance that humans must maintain. The practical implication of this study is the use of literature as a tool for education and public awareness about the importance of protecting the environment. By depicting the beauty and diversity of nature, as well as the negative impacts of environmental damage, these poems can be an effective tool to inspire conservation and conservation actions.